Digital physiotherapy is a satisfactory and effective method to improve the quality of life in Long COVID patients - Estebanez Pérez, María José; Pastora-Bernal, José Manuel; Vinolo-Gil, Maria Jesus; Pastora-Estebanez, Pablo; Martín-Valero, Rocío (SAGE Journals, 2024)
Objective: This research aimed to explore Long COVID patient's quality of life, satisfaction and perception with an individualized and customizable digital physiotherapy intervention during a 4-week period. Methods: A pre-post clinical trial was conducted with 32 Long COVID patients. Quality of life was assessed using the 12-Item Short Form Survey and the European Quality of Life-5 Dimensions questionnaire (EuroQol-5D), while satisfaction and perception were measured using the Telemedicine Satisfaction Questionnaire. Optional open-ended questions were added as qualitative approach. A mixed design method was conducted. Results: After intervention, a statistically significant improvement (p < 0.05) was observed in quality of life. The SF-12 questionnaire showed an increase of 4.04 points in the physical component and 6.55 points in the mental component with a small/medium effect size. The EuroQoL-5D questionnaire demonstrated a medium effect size with an increase of 0.87 points. Patient perception indicated high rates of satisfaction and values above the minimal clinically important difference. The qualitative approach revealed several interesting findings. Conclusion: Participants found the digital intervention satisfactory and effective in improving their quality of life. Suggestions for improvement, such as the inclusion of face-to-face sessions, a chat for immediate contact, sound in breath exercises in the digital program, longer duration and continuity of intervention, were mentioned. Larger sample studies and in-deep qualitative methodologies are needed to draw extrapolable conclusions.
Keywords: Fisioterapia - Innovaciones tecnológicas; Long COVID; digital physiotherapy practice; perception; quality of life; satisfaction